Transient cross-reactive immune responses can orchestrate antigenic variation in malaria. - Recker, M; Nee, S; Bull, P; Kinyanjui, S; Marsh, K; Newbold, C; Gupta, S (2004)
The malaria parasite Plasmodium falciparum has evolved to prolong its duration of infection by antigenic variation of a major immune target on the surface of the infected red blood cell. This immune evasion strategy depends on the sequential, rather than simultaneous, appearance of immunologically distinct variants. Although the molecular mechanisms by which a single organism switches between variants are known in part, it remains unclear how an entire population of parasites within the host can synchronize expression to avoid rapidly exhausting the variant repertoire. Here we show that short-lived, partially cross-reactive immune responses to parasite-infected erythrocyte surface antigens can produce a cascade of sequentially dominant antigenic variants, each of which is the most immunologically distinct from its preceding types. This model reconciles several previously unexplained and apparently conflicting epidemiological observations by demonstrating that individuals with stronger cross-reactive immune responses can, paradoxically, be more likely to sustain chronic infections. Antigenic variation has always been seen as an adaptation of the parasite to evade host defence: we show that the coordination necessary for the success of this strategy might be provided by the host.